Primary mediastinal seminoma presenting with paraneoplastic anti-Hu encephalitis: a case report and literature review - Williams, Chelsey M.; Allison, Derek B.; Coleman, Adam B.; Bardhan, Roshmita; Miller, Jordan D.; Myint, Zin W. (Frontiers in Oncology, 2023)
Primary mediastinal seminomas are exceedingly rare tumors, often localized to the anterior mediastinum. They may present with numerous complications, including superior vena cava syndrome, chylothorax, and pericardial effusions. Less commonly, they may present with paraneoplastic encephalitis. In this report we describe a case of a 19-year-old male with no significant past medical history who presented with bilateral hearing loss, progressive neuropathy, and ataxia. Subsequently the patient was found to have mediastinal mass with a high-titer anti-Hu antibody. To our knowledge, only one other case of mediastinal seminoma presenting with anti-Hu antibodies has been described in the literature. In this report, we describe a rare case of mediastinal seminoma, describe treatment options, and discuss additional known cases presenting with paraneoplastic encephalitis.